The University Teacher: Catalyst of the Emotional-Technological-Ontological Logic in the Teaching of Exact Sciences - Derling Jose Mendoza Velazco; Elizeth Flores (Indo-MathEdu Intellectuals Journal, 2022)
The aim of the study was to design a theoretical approach to the existing techno-ontological logical emotions of university mathematics teachers working in universities in Ecuador. The research was qualitative. For the selection of the sample, a random selection was carried out under the criterion of intentionality. Twenty (20) students and eight (8) mathematics teachers from different universities participated. For data collection, we used a participatory digital observation guide and an open-ended interview. Three categories emerged from the results: the andragogic retrotopia of being a mathematician, the emotional scar in teacher training and the educational perception of the university student. We conclude with a theoretical approach in which the deficit of professional digital training in mathematical sciences allows the emotional logic of the Ecuadorian teacher to drive her to portray an academic being that generates hatred and rejection in the university educational community.